Relationship of the Light Intensity of Selected Light Curing Units with Varying Distance and Agulation of the Light Curing Tip and Lightmeter. - Radzi, Z; Abu Kasim, NH; Yahya, NA; Abu Osman, NA; Abu Kassim , Noor Lide (University of Malaya, 2008)
Background: The purpose of this study was to investigate the light intensity of selected light curing units with varying distance and angulation of the light curing tip and lightmeter. Materials and method: Four types of light units; Spectrum 800 (Dentsply), Coltulux 3 (Coltene), Elipar FreeLight 2 (3M Espe) and Starlight Pro (Mectron) were evaluated for light intensity at various distances between the light curing tip and the radiometer Cure Rite Denstply (0,1,3,5,10 and 15 mm). The light curing units were tested at right angles to the aperture of the light meter and at the angles of 45°, 60° to it at a standardized 5 mm distance. Results: The highest light intensity was obtained when the tip of light curing unit was in contact with the lightmeter aperture. The light intensity decreased significantly when the light tip was placed 5mm, 10mm and 15mm away from the lightmeter aperture. However, no significant differences (p> .05) were detected between Omm, Imm and 3mm. There was a decrease in light intensity when light~·tip was angulated at 45° and 60° except for Coltolux 3. Conclusions: The intensity of the curing light was affected by the distance between the light curing tip and the lightmeter. However, the decrease in light intensity of the light curing unit was found not to obey the inverse square law for the distances 0 to 15 mm. The study found that there was no significant difference between 45° and 60° angulation between the light curing tip and the lightmeter. However, the decrease in light intensity was significant when compared to the light tip placed perpendicular (90°) to the aperture of the light meter.